The role of magnetism in the formation of the two-phase miscibility gap in β Cu-Al-Mn - Lanzini, Fernando Gabriel (2015)
Abstract A theoretical study of the ground state properties of alloys with compositions along the pseudobinary line Cu3Al-Cu2AlMn is presented. Cohesive energies, lattice parameters and magnetic moments of the two limiting compounds and three intermediate compositions are calculated by means of density functional theory. In order to evaluate the role of magnetism, both the spin-polarized (SP) and the non spin-polarized (NSP) cases have been considered. It is shown that magnetism plays a central role on the stabilization of the L21 crystal structure in Cu2AlMn, and in the formation of the miscibility gap in Cu3Al-Cu2AlMn. The considerable lattice mismatch between the end compounds can be attributed also to magnetic effects.